Hours of work risk factors for coal mining. (29th September 2008) - Cliff, David; Horberry, Tim
This paper considers the principal variations in accident and incident risk in relation to roster design within the Australian coal mining industry. Analysing industry-wide accident and incident statistics for both a wide range of coal mine operating conditions and different roster patterns allowed for the impact of hours on shift, number of successive shifts and the type of shift to be evaluated. In general, the obtained results did not indicate any strong association between hours of work and the number of incidents or injuries. Likewise, there was no detectable change in the relative number of severe injuries between shift types.